BACE1 at the crossroads of a vicious circle between Alzheimer’s disease and diabetes mellitus - Ohno, Masuo (Frontiers in Dementia, 2025)
Alzheimer’s disease (AD) and type 2 diabetes mellitus (DM), both of which are characterized by increased prevalence with aging, have considerable overlap in their risk factors, comorbidities and pathophysiological mechanisms including insulin resistance. While Alzheimer’s β-secretase BACE1 is primarily expressed in the brain, it is also present in peripheral tissues at lower levels. Interestingly, BACE1 not only initiates the sequential cleavage of amyloid precursor protein to generate amyloid-β (Aβ) peptides but also cleaves the ectodomain of insulin receptors. Given a growing body of research showing that increased Aβ and insulin resistance elevate BACE1 level/activity, BACE1 represents a key molecule that is situated at the crossroads of a vicious circle between AD and DM. Remarkably, BACE1 level/activity is found to increase under insulin resistance in type 2 DM patients and animal models, which may represent a contributing factor to the progression to AD. This review provides an overview of BACE1 mechanism as a dual disease-modifying therapeutic target to mitigate β-amyloidosis and insulin resistance that underlie cognitive decline at the intersection between AD and DM.